User-aware provably secure protocols for browser-based mutual authentication. (1st September 2009) - Gajek, Sebastian; Manulis, Mark; Schwenk, Jorg
The standard solution for mutual authentication between human users and servers on the internet is to execute a transport layer security (TLS) handshake during which the server authenticates using a X.509 certificate followed by the authentication of the user either with own password or with some cookie stored within the user's browser. However, poor ability of human users to validate X.509 certificates allows for various forms of (social) impersonation attacks. In this paper, we introduce human perceptible authentication (HPA) as a concept for the secure user-aware authentication of servers via recognisable authenticators such as images, video or audio sequences. We formally specify HPA within a security model for browser-based mutual authentication; for this, we extend the traditional Bellare-Rogaway model to deal with human users as inherent protocol participants. Using HPA and the classical TLS handshake, we furthermore design two efficient provably secure password- and cookie-authentication protocols.